1762 R.I. Pub. Laws 132 - (:unkn) unknown (My University, 1762)
An Act of June 1762: That every person who shall import gunpowder into the town of Newport aforesaid shall cause the same to be conveyed immediately to the powder house at the North Easterly part of town, before the vessel in which the said Powder shall be imported, be brought to any Wharf; upon the penalty of paying into the Town-Treasury of the said Town of Newport, a Fine of Ten Shillings Lawful Money, for every cask which shall not be conveyed to the Powder House as aforesaid
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER